If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + -8 = 10y + 2 Reorder the terms: -8 + 15y = 10y + 2 Reorder the terms: -8 + 15y = 2 + 10y Solving -8 + 15y = 2 + 10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10y' to each side of the equation. -8 + 15y + -10y = 2 + 10y + -10y Combine like terms: 15y + -10y = 5y -8 + 5y = 2 + 10y + -10y Combine like terms: 10y + -10y = 0 -8 + 5y = 2 + 0 -8 + 5y = 2 Add '8' to each side of the equation. -8 + 8 + 5y = 2 + 8 Combine like terms: -8 + 8 = 0 0 + 5y = 2 + 8 5y = 2 + 8 Combine like terms: 2 + 8 = 10 5y = 10 Divide each side by '5'. y = 2 Simplifying y = 2
| 5x+7=3(x+4) | | .74=11612000-x/5246000 | | 1+192837465x-d=231111111116666666 | | 4/b-7/d= | | 55x-9+g=100007 | | 4/(x-6)=5 | | 55x-9+g= | | 3t+19-5t=91 | | z^2(4z^3-10)=0 | | u/4=0 | | 5p^2+30x=0 | | 4x-1=2(x-5) | | 5c+17-8c=156 | | 2=p/6 | | 5/60=w/10 | | 4x-1=2(x-3) | | 345=874-x/874 | | 9r+9= | | 2x-1/4x=(-28) | | 3/4d=18 | | 7(x+8)+4=-9(x-9)-1 | | 2s+a=447 | | 3/8d=6 | | X+11x+2=0 | | 3(4x+1)=9(3x-5) | | 6x-4=5(x+3)+7 | | 3x^2-18x=48 | | 81x^3+324x^2-x-4=0 | | 7x-8-4x=25 | | y=-3/5x-4/5 | | (3+x)3=9 | | 2x-13=7*12 |